2014
DOI: 10.1155/2014/510343
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Diaspore Characteristics with Phylogeny, Life History Traits, and Their Ecological Adaptation of 150 Species from the Cold Desert of Northwest China

Abstract: Diaspore characteristics of 22 families, including 102 genera and 150 species (55 represented by seeds and 95 by fruits) from the Gurbantunggut Desert were analyzed for diaspore biological characteristics (mass, shape, color, and appendage type). The diaspore mass and shape were significantly different in phylogeny group (APG) and dispersal syndromes; vegetative periods significantly affected diaspore mass, but not diaspore shape; and ecotypes did not significantly affect diaspore mass and shape, but xerophyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
(51 reference statements)
0
18
1
Order By: Relevance
“…Some awns have stiff hairs or thorns on their surface that help provide unidirectional "ratcheting" movement for seeds ( Elbaum et al, 2007 ;Kulic et al, 2009 ). In some cases, awns react with water to increase seed burying depth through spiraling or "drilling" motions ( Garnier and Dajoz, 2001 ;Elbaum et al, 2007 ;Johnson and Baruch, 2014 ;Liu et al, 2014 ). In many cases, this increased burial depth can lead to increased survival aft er fi re ( Garnier and Dajoz, 2001 ;Johnson and Baruch, 2014 ).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Some awns have stiff hairs or thorns on their surface that help provide unidirectional "ratcheting" movement for seeds ( Elbaum et al, 2007 ;Kulic et al, 2009 ). In some cases, awns react with water to increase seed burying depth through spiraling or "drilling" motions ( Garnier and Dajoz, 2001 ;Elbaum et al, 2007 ;Johnson and Baruch, 2014 ;Liu et al, 2014 ). In many cases, this increased burial depth can lead to increased survival aft er fi re ( Garnier and Dajoz, 2001 ;Johnson and Baruch, 2014 ).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…In many cases, this increased burial depth can lead to increased survival aft er fi re ( Garnier and Dajoz, 2001 ;Johnson and Baruch, 2014 ). Additionally, some awns can cling to animal fur or feathers to increase zoonotic dispersal ( Liu et al, 2014 ). Many awns have dense numbers of stomata, leading to high rates of transpiration and, in some species, photosynthesis, which can increase seed mass ( Grundbacher, 1963 ).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Hence, seed characteristics of species in this desert are diverse and complex [ 30 ]. Previous studies showed that diaspore mass and shape differed significantly among phylogenetic groups and dispersal syndromes in this desert [ 31 ]. However, germination strategies as well as seed dispersal strategies of species are adaptations to the desert environment, but very little is known about the relationship of seed dispersal and germination strategies in deserts (but see [ 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizosheath-related microorganisms of desert plants can promote plant growth and enhance stress tolerance, especially nitrogen-fixing related microorganisms (10,11). Stipagrostis pennata (Gramineae) has advantages in effectively resisting long-distance diffusion and occupying the surrounding optimized environment (12). Our previous experimental results show that the strategy of stipagrostis pennata against harsh environment is related to the nitrogen fixation ability of root sheath (13).…”
Section: Introductionmentioning
confidence: 97%